2019
DOI: 10.31234/osf.io/827pg
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Racial Microaggression, Overt Discrimination, and Distress: (In)Direct Associations with Psychological Adjustment

Abstract: P. Priscilla Lui, Racial microaggression, overt discrimination, and distress:(In)Direct associations with psychological adjustment, The Counseling Psychologist. AbstractSeparate literatures have examined the associations between psychological adjustment and microaggression, and overt discrimination; whether microaggression is related to adjustment outcomes above and beyond overt discrimination and neuroticism remains unclear. I examined the extent to which racial microaggression explained unique variances of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 37 publications
1
25
0
Order By: Relevance
“…Individual difference factors have been shown to shape people’s worldviews and reactions to interracial exchanges. For example, colorblind attitudes accounted for variability in how Whites evaluated racism and discrimination-related events; neuroticism also explained individual differences in the associations between discrimination and mental health outcomes [ 29 , 63 , 64 ]. Future research should systematically examine how individual difference factors including racial identity, colorblind attitudes, and prior discrimination-related experiences might shape people’s attitudes toward microaggressions and reactions to discrimination events.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Individual difference factors have been shown to shape people’s worldviews and reactions to interracial exchanges. For example, colorblind attitudes accounted for variability in how Whites evaluated racism and discrimination-related events; neuroticism also explained individual differences in the associations between discrimination and mental health outcomes [ 29 , 63 , 64 ]. Future research should systematically examine how individual difference factors including racial identity, colorblind attitudes, and prior discrimination-related experiences might shape people’s attitudes toward microaggressions and reactions to discrimination events.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the exposure to other adverse events such as bullying [ 28 ], it should not be surprising that individuals might react to microaggression—and other racism-related experiences—differently based on their personal characteristics. Nevertheless, within POC groups, racial microaggression experiences were linked to psychological outcomes over and above trait neuroticism [ 29 , 30 ]. Research also showed that POC’s health outcomes were disproportionately affected by discrimination and microaggression not because of people’s hypersensitivity to racism; rather, POC were more likely to experience differential treatment relative to Whites [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…People of color experience unique stressors related to their marginalized social identity that adversely contribute to depression and anxiety (57), including explicit racial/ethnic discrimination and microaggressions (58)(59)(60)(61). Intergenerational trauma created by American slavery, colonialism, Jim Crow laws, and segregation, has been shown to effect both physical and psychological health among Black people (62)(63)(64).…”
Section: The Relationship Between Racial/ethnic Discrimination and Symentioning
confidence: 99%
“…Nevertheless, within POC groups, racial microaggression experiences were linked to psychological outcomes over and above trait neuroticism [29,30]. Research also showed that POC's health outcomes were disproportionately affected by discrimination and microaggression not because of people's hypersensitivity to racism; rather, POC were more likely to experience differential treatment relative to Whites [31].…”
Section: Racism Discrimination and Microaggressionmentioning
confidence: 99%